The serological survey on bovine adenovirus type 2 infection in bovine in konya - Feridun Öztürk; Sibel Yavru; Rüstem Duman; Atilla Şimşek (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine serologically the bovine adenovirus (BA V) type 2 infections on 950 cattle blood sera in Konya. The cattle blood sera collected from 950 cattle in Meat and Fish Association's Slaughterhouse in Konya, were subjected to microneutralization test, initially by diluting 1/10, then by diluting them two times and by comparing BAV type 2 viruses with the ratio of 100 DKID501.05 ml. MDBK (Madine Darby Bovine Kidney) cell culture were used in virus production, in titration and in microneutralization test. As a cell medium, Eagle's MEM with % 10 inactivated calf sera and as virus medium Eagle's MEM medium without sera were used. Based on the results the neutralization antibodies were found in 247 sera of the 950 sera against BAV type 2. This study pointed out that the adenovirus infections were prevalent in cattle in Konya.